ANALISIS FINANSIAL DAN SENSITIVITAS AGROINDUSTRI EMPING MELINJO SKALA USAHA MIKRO, KECIL DAN MENENGAH (UMKM) - Fitria M. Fitria M.; Muhammad Irfan Affandi; Adia Nugraha (Lampung University, 2013)
The research was conducted in Bernung village of Gedong Tataan Sub-district of Pesawaran Regency and Rajabasa village of Rajabasa Sub-district of Bandar Lampung City. The two location were selected purposively based on the consideration that many emping melinjo craftsmen existed in these villages in which melinjo materials stock were supplied sufficiently. The research used primary and secondary data of the 37 respondents. The data was collected in July until August 2012 and was analyzed by financial feasibility the NPV, IRR, Net B/C, Gross B/C, Payback Period, BEP and sensitivity. The results showed that emping melinjo agroindustries in Bernung village and in Rajabasa village were financially feasible to develop and profitable, with NPV 90.605.605,92 and 25.974.416,60, IRR of 50,84 % and 38,20 %, Net B/C 7,34 and 3,66, Gross B/C 1,13 and 1,22, and PP 5,36 and 5,41. Keywords: agroindustry, emping melinjo, feasibility, financial feasibility